Unlocking Trade for Low-Income Countries : Report of the Trade Facilitation Facility, 2009-2015 - World Bank Group (World Bank, Washington, DC, 2016)
The trade facilitation facility (TFF) was launched to help low-income countries improve their competitiveness by reducing the costs of engaging in international trade, thus supporting their efforts to reduce poverty and achieve the millennium development goals. This report summarizes the outcomes of the TFF between its establishment in 2009 and its end in 2015. The report highlights and reviews the accomplishments and lessons learned of TFF; it also discusses and reflects the perspective of task team leaders and relevant World Bank Group officials on the Bank Group’s continuing work in the trade facilitation sphere. The report presents results of TFF-funded activities and programs managed by staff from a large cross section of Bank Group sectors, including transport, agriculture, governance (customs), international trade, and private sector development. The report is organized as follows: chapter one give introduction. Chapter two provides an overview of the TFF portfolio. Chapter three looks at TFF as enabler of deepening regional integration, highlighting some of the facility’s accomplishments from a geographic and thematic perspective, particularly the extent to which TFF complemented Bank infrastructure operations and nurtured progress on trade facilitation instruments that countries and regional economic communities (RECs) have adopted but failed to implement. Chapter four, expanding thematic insights, addresses conceptual themes in trade facilitation. Chapter five, conclusions and contributions, sums up the areas in which TFF has contributed to moving the regional and multilateral trade facilitation agenda.